2014
DOI: 10.1373/clinchem.2013.215251
|View full text |Cite
|
Sign up to set email alerts
|

Circulating 25-Hydroxyvitamin D, IRS1 Variant rs2943641, and Insulin Resistance: Replication of a Gene–Nutrient Interaction in 4 Populations of Different Ancestries

Abstract: BACKGROUND Associations of either insulin receptor substrate 1 (IRS1) variants or circulating 25-hydroxyvitamin D [25(OH)D] with type 2 diabetes (T2D) and insulin resistance (IR) are inconsistent. This study sought to determine whether circulating 25(OH)D modulates the association of a potentially functional variant at IRS1 (rs2943641) with insulin resistance. METHOD Interaction between IRS1 rs2943641 and circulating 25(OH)D on homeostasis model assessment for IR (HOMA-IR) was examined in the Boston Puerto R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Comparatively speaking, Western European people have a better nutritional status, which may account for a higher frequency of the TT genotype. Thus, the phenomenon of gene-nutrient interaction can partly explain the discrepant allele distribution among different ethnicities 73 . On the other hand, we noted that the sample size and numbers of studies in American and African groups were not ample, which might result in mistaken conclusions 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively speaking, Western European people have a better nutritional status, which may account for a higher frequency of the TT genotype. Thus, the phenomenon of gene-nutrient interaction can partly explain the discrepant allele distribution among different ethnicities 73 . On the other hand, we noted that the sample size and numbers of studies in American and African groups were not ample, which might result in mistaken conclusions 74 .…”
Section: Discussionmentioning
confidence: 99%
“…IRS-1) and vitamin D status (e.g. those involved in skin production of vitamin D, in vitamin D-binding protein concentrations and vitamin D catabolism) may also alter treatment response [38] . Finally, baseline calcium intake may also affect response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also explored the relationship between the insulin receptor substrate 1 (IRS1) variant rs2943641 and circulating levels of 25-hydroxyvitamin D (25(OH)D). Women homozygous for the minor allele rs2943641T with higher circulating 25(OH)D showed a lower risk of insulin resistance and T2DM compared to carriers of the major allele (rs2943641C) [ 61 ] ( Table 2 ). Gene-whole grain intake interactions have also been established for the glucokinase regulatory protein (GCKR) variant rs780094 in a meta-analysis of 14 cohort studies; this study demonstrated that dietary whole grain intake potentially interacts with the cited variant.…”
Section: Gene-nutrient or Dietary Pattern Interactions In The Devementioning
confidence: 99%